The Evaluation of 16-Channel Hybrid ASE and LED WDM-PON System Performance - Lasuks, I. (Elektronika ir Elektrotechnika, 2011)
The worldwide demand of bandwidth has led to the expansion of fiber optics access technologies. However, TDM-PON (Time Division Multiplexing PON) concept has its limitations due to the concept of time division. Another way of increasing the bit rate is WDM-PON (Wavelength Division Multiplexing PON) solution. To satisfy the growing demand the system must have high bit rate and be cost-effective. Spectral-slicing technique can achieve this aim. ASE-source (Amplified Spontaneous Emission) as the OLT (Optical Line Terminal) and colorless LED (Light Emitting Diode) as ONU (Optical Network Unit) hybrid solution is proposed in this paper. In this paper is demonstrated 16 channel WDM-PON system with optical slicing technique. All the central wavelength conversions are made with the help of spectral slicing in the AWG (Arrayed Waveguide Grating) with FSR (Free Spectral Range). Ill. 8, bibl. 5, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.440